Pemberdayaan Komunitas dan Peningkatan Kesadaran Lingkungan Melalui Program Jumat Bersih di Desa Nekmese - Vinsensius Jago; Yanuarius Rendy Petty; Indriyati Indriyati; Hendrikus Likusina Kaha; Stephanie Perdana Ayu Lawalu; Yohannes K. Ethelbert (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
Environmental hygiene conditions in rural areas of eastern Indonesia face complex challenges due to limited infrastructure and low community participation in environmental management. Baseline data in Nekmese Village shows that only 6.2% (20 out of 325 heads of families) are active in routine cleaning activities, while three strategic locations (village office, spring, and sports field) experience degradation in cleanliness quality that threatens public health. This study analyzes the effectiveness of socio-ecological interventions through the Clean Friday program based on the Participatory Rural Appraisal (PRA) approach in improving environmental quality and strengthening social cohesion. Implementation was carried out for four weeks (April 9-29, 2025) involving 325 heads of families through participatory observation, in-depth interviews, and systematic documentation. The results show a measurable increase in community participation from 20 participants (6.2%) in the first week to 50 participants (15.4%) in the fourth week, with a growth rate of 150% and statistical significance p0.05. Environmental quality evaluation using the Environmental Quality Index (EQI) showed an increase in scores from 2.1 to 3.8 (on a scale of 1-5) at all three target locations. These findings confirm the Social Learning Theory, which posits that collective participation can change environmental behavior through observational learning and social reinforcement. The practical contribution of this research lies in the development of a community-based intervention model that can be replicated in areas with similar geographic and socio-economic characteristics, particularly in the context of sustainable socio-ecological capacity development.